Development of Instructional Media “Game Math Comic Story” Based Android on Number - Sulistio, Wahyu; Qohar, Abd (LPPM Undiksha, 2020)
This research was conducted with the purpose to produce mathematics instructional media based game and comic stories for android. This study aimed at assisting students in studying number material and increasing reading interest for 7th grade students. Media developed were stories that were made into an adventure game made with